KUASA WACANA KEBUDAYAAN BUGIS MAKASSAR DALAM PILKADA DI KABUPATEN PINRANG (STUDI KASUS: IMPLEMENTASI NILAI-NILAI SIPAKATAU, SIKAINGE’ DAN SIPAKALEBBI DALAM MEMOBILISASI MASSA PADA PILKADA PINRANG TAHUN 2013) - RAZAK, FITRIANI SARI HANDAYANI (Department of Political Science, Universitas Islam Negeri Alauddin Makassar, 2015)
This article outlines the existence of cultural values in shaping behavior of political elites in seizing power or in election campaign process in Pinrang in 2013. In one hand, some people romantically treat culture as heritage for the sake of today and future society to realize and for functioning as a guide in establishing an ideal pattern of community life. On the other hand, there are some deviating practices, which have never been revisited.